Pertimbangan Hakim Memutus Akta Hibah Yang Dikeluarkan Oleh Pejabat Pembuat Akta Tanah Tidak Mempunyai Kekuatan Hukum (Studi Putusan Mahkamah Agung Tahun 2009 – 2017) - Jannah, Siti Khurfatul (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2021)
The judge's consideration is the most important aspect in determining the realization of the value of justice (ex equo et bono) and the legal certainty of a judge's decision. In this paper, we will discuss the decision on grant disputes determined by the judges of the Supreme Court. This research is normative legal research, with a conceptual approach. The data sources in this study are secondary data sources consisting of primary and secondary legal materials, which will be analyzed qualitatively. In this study, data were obtained from the Directory of Decisions of the Supreme Court of the Republic of Indonesia which informed that there were 369 cases of application for cancellation of grants that had been decided by the Supreme Court. And from these decisions, many decisions stipulate that the deed of grant is declared to have no legal force. Therefore, it is necessary to know the reasons that make the grant deed declared invalid and the consequences for the parties related to the legal act of the grant. From the results of the discussion, it is known that, although the provisions of grants according to Islamic law in Indonesia have been regulated in the KHI, the implementation of grants and grant deeds made by PPAT does not pay attention to the existing legal provisions. So that it is declared that it has no legal force by a judge of the Supreme Court, and it must be returned to its original position.